Congenital anomalies in children with cerebral palsy in rural Bangladesh. (6th January 2020) - Manlongat, Ellen; Mcintyre, Sarah; Smithers‐Sheedy, Hayley; Trivedi, Amit; Muhit, Mohammad; Badawi, Nadia; Khandaker, Gulam
Abstract : Aim: To determine the proportion of children with cerebral palsy (CP) who had major congenital anomalies, describe the types of disorders, and report on the children's functional outcomes. Method: Data were extracted from the Bangladesh Cerebral Palsy Register (BCPR). Descriptive analyses were conducted on children with CP and major congenital anomalies. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to measure the association between major congenital anomalies, clinical severity, and presence of comorbidities. Results: Between January 2015 and December 2016, 726 children with CP were newly registered with the BCPR (277 females, 449 males; mean age [SD] at registration 90mo [54mo], 4mo–18y). Seventy‐eight children (11%) had a major congenital anomaly. Neurological (86%) and musculoskeletal congenital anomalies (10%) were the most common. Microcephaly was the most common congenital anomaly (83%). The odds of severe functional motor limitations (OR=2.4, 95% CI=1.9–2.9), epilepsy (OR=1.6, 95% CI=1.1–2.1), visual impairment (OR=2.6, 95% CI=2.0–3.2), presence of strabismus (OR=3.9, 95% CI=3.8–4.4), hearing (OR=1.2, 95% CI=0.6–1.9), speech (OR=5.4, 95% CI=4.6–6.2), and intellectual impairments (OR=2.3, 95% CI=1.8–2.8) were higher in children with congenital anomalies compared to children without. Interpretation: The proportion of children with major congenital anomalies in the BCPR (11%) was lower than that identified in higher‐income countries. This may be because of differences in how congenital anomalies are diagnosed as well as the impact of survival bias. In Bangladesh, children with CP and major congenital anomalies are more likely to have severe functional motor limitations and associated comorbidities. What this paper adds: Eleven per cent of children with cerebral palsy (CP) in Bangladesh had major congenital anomalies. Neurological and musculoskeletal congenital anomalies were the most common. Severe functional motor limitations and associated comorbidities were more common in children presenting with CP and major congenital anomalies. What this paper adds: Eleven per cent of children with cerebral palsy (CP) in Bangladesh had major congenital anomalies. Neurological and musculoskeletal congenital anomalies were the most common. Severe functional motor limitations and associated comorbidities were more common in children presenting with CP and major congenital anomalies. This article is commented on by Bedard on page 408 of this issue.